KONSEP PENDIDIKAN JERMAN DAN AUSTRALIA - Saifullah Isri (Jurnal Ilmiah Peuradeun, 2014)
Education system for a nation to be essentially in accordance with the philosophy and culture itself. Taking over a system or idea in the field of education of other nations must be assessed by the application of existing cultural backgrounds. Therefore, to compare the educational systems of Germany and Australia also we need to adapt to the culture and philosophy of the nation. It is interesting in this discussion is the implementation of the education in the world has a different implementation in each country, so that it can be a barometer in improving the quality of education. In this paper writer try to educate how the structure of education and type of education, education management system, the system of education management organizations, educational assessment system, the financing of education and academic degrees as applicable comparative study of German and Australian education to improve the quality of education in Indonesia.